Penyuluhan dan deteksi dini kanker serviks menggunakan teknik sitologi Pap Smear konvensional - Maulani, Heni; Kartika, Ika; Murti, Krisna; Wresnindyatsih, Wresnindyatsih (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Cervical cancer is still the second biggest cause of mortality in women in Indonesia. Pap Smear cytology can detect precancerous lesions as precursor lesions early. Every married woman should have a Pap Smear examination done on a regular basis. If precancerous lesions are discovered, they must be treated immediately so that they do not proceed to cervical cancer. Counseling and Pap Smear Examination will be used to carry out the activity, which is aimed at all married women. The goal of this activity is to raise public awareness about the necessity of early cervical cancer screening and Pap Smear examination for early diagnosis of cervical precancerous lesions. Pre-test and post-test assessments were used to establish the degree of knowledge of participants. Counseling and examination activities was place four times in September-October 2021, at the Gandus Health Center and the practice of midwife Hj. Nani. This community service has attracted 130 counseling participants. Participants' understanding of the importance of early identification of cervical cancer increased from a score of 75.57 to 89.28 as a result of the pretest and post-test counseling outcomes. According to the Pap Smear diagnostic results, the majority of patients had non-specific chronic cervicitis, which was classified as Negative for Intraepithelial Lesion or Malignancy (NILM). Cervical cancer can be prevented with counseling and early detection.